The reading strategies book : your everything guide to developing skilled readers - Serravallo, Jennifer (Portsmouth, NH : Heinemann, 2015)
With hit books that support strategic reading through conferring, small groups, and assessment, Jen Serravallo gets emails almost daily asking, "Isn't there a book of the strategies themselves?" Now there is. "Strategies make the often invisible work of reading actionable and visible," Jen writes. In The Reading Strategies Book, she collects 300 strategies to share with readers in support of thirteen goals -- everything from fluency to literary analysis. Each strategy is cross-linked to skills, genres, and Fountas & Pinnell reading levels to give you just-right teaching, just in time. With Jen's help you'll develop goals for every reader, give students step-by-step strategies for skilled reading, guide teachers with prompts aligned to the strategies, adjust instruction to meet individual needs with Jen's Teaching Tips, craft demonstrations and explanations with her Lesson Language, and learn more with Hat Tips to the work of influential teacher-authors. Whether you use readers workshop, Daily 5/CAFE, guided reading, balanced reading, a core reading program, whole-class novels, or any other approach, The Reading Strategies Book will complement and extend your teaching. Rely on it to plan and implement goal-directed, differentiated instruction for individuals, small groups, and whole classes. "We offer strategies to readers to put the work in doable terms for those who are still practicing," writes Jen Serravallo. "The goal is not that they can do the steps of the strategy but that they become more comfortable and competent with a new skill." With The Reading Strategies Book, you'll have ways to help your readers make progress every day. Visit heinemann.com/readingstrategiesbook/ where you'll find blog posts, videos from Jen Serravallo, community features, and more information on The Reading Strategies Book.--Publisher.
Supporting pre-emergent and emergent readers -- Teaching reading engagement : focus, stamina, and building a reading life -- Supporting print work : increasing accuracy and integrating sources of information -- Teaching fluency : reading with phrasing, intonation, and automaticity -- Supporting comprehension in fiction : understanding plot and setting -- Supporting comprehension in fiction : thinking about characters -- Supporting comprehension in fiction : understanding themes and ideas -- Supporting comprehension in nonfiction : Determining main topic(s) and idea(s) -- Supporting comprehension in nonfiction : determining key details -- Supporting comprehension in nonfiction : getting the most from text features -- Improving comprehension in fiction and nonfiction : understanding vocabulary and figurative language -- Supporting students' conversations: speaking, listening, and deepening comprehension -- Improving writing about reading.
Includes bibliographical references (pages 379-388).
Keywords: Reading; Books and reading; Books and reading; Reading